Physical and mechanical properties Of Bio-Composite board from compressed oil Palm Fronds - Mohd Sukhairi Mat Rasat; Razak Wahab; Ag Ahma; AG Ahmad Mohd Yunus; Janshah Moktar; Sitti Fatimah Mhd. Ramle; Zulhisyam Abdul Kari @ Abdullah; Mahani Yusoff (2013)
Investigations were on physical and mechanical properties of the bio- composite boards made from compressed oil palm fronds. The bio-composites board consits of young, intermediate and mature fronds, which were divided to three portions respectively. They were the bottom, middle and top portions for each maturity age group of the fronds. The fronds were sliced longitudinal into the thin sheet after their skins were removed. The sheets were later compressed by running them through a flattening machine. Two types of resins namely phenol formaldehyde and urea formaldehyde were used to bind the fronds's sheets together forming parallel bio-composite board from compressed oil palm fronds. The physical and mechanical properties of this bio-composite board were later studied. the physical and mechanical properties of this bio-composite board were later studied. The physical properties such as density and basic density were investigated. The mechanical properties such as static bending for modulus of elasticity and mudulus of rupture as well as the compression strengh for modulus of rupture were studied in order to investigate their strength properties in structural application. All tests were made in accordance to the International Organizational for Standardization (ISO) standards.The results indicate that the bio-composite boards with higher basic density possess higher bending and compression strenght compares to those with lower values. The bio-composite board from bottom portion oil palm frond shows to have the higher basic density follows by the middle and top portion for each maturity age group, meanwhile matured maturity group possess the higher basic density for each portion compare to the intermediate and young maturity group. Thus, the bending and compression strength show to have higher results for bio-composite board from bottom portion and decrease for the middle and top portion for each maturity age group, while the matured maturity group posses the higher strenght result for each portion follows then by intermediate and young maturity group.